Development of immunohistochemistry and enzyme-linked immunosorbent assays for the detection of circulating antibodies against Enteromyxum scophthalmi (Myxozoa) in turbot (Scophthalmus maximus L.) - Sitjà-Bobadilla, Ariadna; Redondo, Mª José; Macías, M. A.; Ferreiro, Isabel; Riaza, Ana; Álvarez-Pellitero, Mª del Pilar (Fish & Shellfish Immunology, 2004)
Immunohistochemistry and enzyme-linked immunosorbent assays were developed for the detection of specific antibodies against the myxosporean parasite Enteromyxum scophthalmi in turbot (Scophthalmus maximus L.). Fish which had survived a previous epizootic were exposed to the parasite by cohabitation with infected animals, and 83 days later the plasma was tested for the presence of antibodies. Plasma of non-exposed fish was used as negative control. Immunohistochemistry (IHC) using rabbit anti-turbot IgM antibody was first used to detect these antibodies, and to study to which parasite structures they were directed against. Also, an antibody-ELISA using whole cell lysates of the parasite as antigen, and a monoclonal antibody anti-turbot IgM, was developed. All the exposed fish were found to have specific antibodies against the parasite, and none of them developed signs of disease or died during the experiment. Primary cells were the main parasite stage immunolabelled, and the staining was distinctly located on the cytoplasm and the cytoplasmic membrane. IHC was more sensitive than ELISA, as the endpoint was two to four fold higher with the former technique. Although there was great individual variation, the antibody titres found can be considered high, reaching up to 1:32,000 with ELISA and 1:64,000 with IHC. The results suggest that turbot showing acquired immunity against E. scophthalmi, could develop resistance against new infections. This study was funded by the FEDER research grant 1FD97-0679-C02-01 (European Union, Spanish Government and Stolt Sea Farm, S.A.) and research project AGL2001-2241-C01-01 (Spanish Ministry of Science and Technology). Additional funding was provided by Stolt Sea Farm, S.A. through a research contract. We are grateful to J. Monfort for the histological processing, and to Dr. M.I. Quiroga from the Veterinary Faculty of Lugo (University of Santiago) for providing some paraffin blocks.